Prevalence, Knowledge, and Attitudes towards Herbal Medicine Use during Pregnancy among Women Attending Antenatal Care in Derna and Tobruk, Libya: A Cross-Sectional Study - Akrim, Taweda; EL HEMIEDY, REHAB; Mohamed, Mostafa (Sharwes Scientific Journal, 2025)
Herbal medicine (HM) use during pregnancy presents both cultural continuity and potential clinical risk, particularly where biomedical engagement is limited or fragmented. Although global evidence highlights the widespread use of herbal remedies among expectant mothers, Libyan populations remain underrepresented in such epidemiological assessments. This cross-sectional study investigated the prevalence, knowledge, and attitudes related to HM use, and examined associations with sociodemographic and informational variables among 1,500 pregnant women attending antenatal clinics in Derna and Tobruk. Data were collected through a structured questionnaire addressing demographic characteristics, herbal usage patterns, source of information, and safety awareness. Analysis revealed that lower educational attainment and reduced household income were significantly associated with increased herbal use (p < 0.01). Multiparous women reported higher usage rates than primigravidae (OR = 2.18, p = 0.003), and reliance on informal sources—particularly family advice—was strongly linked to lack of knowledge regarding herb–drug interactions and trimester-specific risks. These findings suggest that traditional health practices are shaped by structural inequities, cultural trust, and gaps in formal antenatal communication. The results underscore the need for culturally sensitive, early-pregnancy health education interventions that engage directly with herbal practices and promote safe maternal decision-making.